Independence in Daily Activities and Living with Family: Predictors of Gratitude in Elderly with Disability in Indonesia - The Maria Meiwati Widagdo; Novita Eveline Tjuluku; Maria Fransiska Pudjohartono; Bernadeta Dhaniswara Widyaningsih (Iranian Journal of Nursing and Midwifery Research)
Background: While aging is associated with health decline leading to disability, gratitude is vital for it has positive impacts on health, both mentally and physically. Being grateful reduces stress, lowers blood pressure, and improves sleep patterns. The study aimed to identify variables associated with gratitude in elderly with disability. Materials and Methods: This research was a descriptive analytical cross-sectional study. Respondents were people aged 60 years and over with disability. They were recruited using purposive sampling. Data on demography, living arrangements, self-reported diseases, age at disability onset, disability (assessed using Washington Group Short of Questions on Functioning), independence in daily activities [assessed using Activities of Daily Living and Instrumental Activities of Daily Living (IADL) questionnaires], and gratitude (measured with a questionnaire) were collected from the respondents. Multivariate linear regression analysis with a stepwise method was used to identify variables significantly correlated with gratitude. Results: Fifty-five older people aged 60–90 years participated in the study. The respondents had mobility, speech, hearing, or speech impairment. The stepwise linear regression showed that IADL and living arrangement explained 40% variance in the gratitude with F = 17.99, p < .001 (R2=0.40). Independence in instrumental daily activities and living with family were positively associated with gratitude in elderly with disability. Conclusions: Independence in daily activities and living arrangement are significant factors associated with gratitude in elderly with disability. The findings suggest priority be given to those living alone and needing help for daily activities. Exercise to increase gratitude can be incorporated into holistic care of elderly.